2004
DOI: 10.1016/s1015-9584(09)60066-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Actinomycosis Presenting as a Liver Tumour: Case Report and Literature Review

Abstract: Hepatic actinomycosis poses a difficult problem in both diagnosis and management. We report the management of a patient with isolated hepatic actinomycosis, and review the clinical features and management of patients with hepatic actinomycosis mimicking liver tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…The typical histological lesions and the specific staining properties of lesion-associated sulphur granules make histology the most powerful and rapid diagnostic tool for pulmonary actinomycosis. Actinomycotic sulphur granules are peculiarly characterized by numerous bacterial filaments, surrounded by a striking Splendore-Hoeppli reaction that result specifically positive to gram and PAS staining, but negative to Fite's staining method for acid fast bacteria (Hotchi and Schwarz 1972;Murakami et al 1997;di Tommaso et al 1998;Ramos-Vara et al 1998;Lai et al 2004). These staining properties represent the fundamental criteria for the differential diagnosis of actinomycosis from nocardiosis and botryomycosis in which bacterial clusters may simulate actinomycosis through the formation of analogous sulphur granules within the pyogranulomatous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The typical histological lesions and the specific staining properties of lesion-associated sulphur granules make histology the most powerful and rapid diagnostic tool for pulmonary actinomycosis. Actinomycotic sulphur granules are peculiarly characterized by numerous bacterial filaments, surrounded by a striking Splendore-Hoeppli reaction that result specifically positive to gram and PAS staining, but negative to Fite's staining method for acid fast bacteria (Hotchi and Schwarz 1972;Murakami et al 1997;di Tommaso et al 1998;Ramos-Vara et al 1998;Lai et al 2004). These staining properties represent the fundamental criteria for the differential diagnosis of actinomycosis from nocardiosis and botryomycosis in which bacterial clusters may simulate actinomycosis through the formation of analogous sulphur granules within the pyogranulomatous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of liver actinomycosis case reports, the most common symptoms were non-specific, including fever (83.3%), abdominal pain (74.5%), and weight loss (50.9%) [5]. Because imaging studies frequently reveal single or multiple lesions, actinomycosis is often misdiagnosed as a primary or metastatic tumor.…”
Section: Figure Dynamic Magnetic Resonance Imaging Examination Of Thmentioning
confidence: 99%
“…Treatment of hepatic actinomycosis consists of prolonged antibiotics after surgical debridement and drainage [5]. Penicillin G is the most frequently used antimicrobial to treat actinomycosis, but we chose ampicillin injection as an initial treatment due to a penicillin G shortage.…”
Section: Figure Dynamic Magnetic Resonance Imaging Examination Of Thmentioning
confidence: 99%
“…The medical treatment regimen is the administration of penicillin, tetracycline, or clindamycin [4]. Duration of treatment is variable with courses lasting from 3-6 months and it go until 18 months [7]. Surgery should be reserved for the cases in which percutaneous drainage is not possible [7].…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…Duration of treatment is variable with courses lasting from 3-6 months and it go until 18 months [7]. Surgery should be reserved for the cases in which percutaneous drainage is not possible [7]. A review of the literature by Wong et al showed that in one series, 28 of 53 cases were managed with antibiotics alone and only two of these required surgical intervention.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%